Hybrid Organic/Inorganic Thin‐Film Multijunction Solar Cells Exceeding 11% Power Conversion Efficiency. (7th January 2015) - Roland, Steffen; Neubert, Sebastian; Albrecht, Steve; Stannowski, Bernd; Seger, Mark; Facchetti, Antonio; Schlatmann, Rutger; Rech, Bernd; Neher, Dieter
<x xml:space="preserve">Abstract</x> Hybrid multijunction solar cells comprising hydrogenated amorphous silicon and an organic bulk heterojunction are presented, reaching 11.7% power conversion efficiency. The benefits of merging inorganic and organic subcells are pointed out, the optimization of the cells, including optical modeling predictions and tuning of the recombination contact are described, and an outlook of this technique is given. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>